THE CONCEPT OF "PEACE" IN ENGLISH AND UZBEK NATIONAL CULTURE - Solijonova Dildorakhon Abdurashid qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This thesis analyzes the linguocultural characteristics of the concept of "peace" in English and Uzbek national cultures. The study comparatively studies the expression of the concept of peace in folk thought, proverbs, literary works, and national values. It also highlights the similarities and differences in the cultures of the two peoples.